Deciphering drought response mechanism in Tibetan qingke through comprehensive transcriptomic and physiological analysis - Jiang, Deyuan; Chen, Shuaihao; Qin, Zhongmengyi; Bo, La; Niu, Liping; Zhou, Hongkang; Wang, Jing; Dondup, Dawa; Hou, Xin (Frontiers in Plant Science, 2025)
Qingke (Hulless barley, Hordeum vulgare L. var. nudum) is a key agroecological crop on the Qinghai-Tibet Plateau and other high-altitude regions. Beyond being food crop, it has industrial applications, including livestock forage, brewing, food processing, and biomass fuel conversion, with emerging evidence indicating the presence of pharmacologically active compounds. Qingke has evolved remarkable adaptations to extreme environments, including high-altitude acclimatization, resistance to drought and wind, cold tolerance, nutrient deficiency resilience, and a short growth cycle. With the intensification of global warming, drought stress has become a major abiotic factor limiting qingke productivity. However, the molecular mechanisms underlying its drought response remain largely unexplored. This study conducted a comparative transcriptomic analysis of six qingke cultivars (three drought-tolerant and three drought-sensitive) under controlled drought conditions, with antioxidant enzyme activities monitoring. Differential expression analysis revealed 4,731 drought-responsive DEGs in drought-sensitive cultivars and 3,875 in drought-tolerant cultivars. Further, weighted gene co-expression network analysis (WGCNA) identified gene modules strongly correlated with photosynthetic efficiency parameters (e.g., net photosynthetic rate and transpiration rate), chlorophyll fluorescence parameters (e.g., Fv/Fm and NPQ), ROS-related parameters, and plant growth-related parameters (e.g., plant height and fresh weight). Key genes involved in drought stress, including HvASPR, HvHAB1, HvHVA22, and HvPUT5, were identified. Their effectiveness in enhancing drought resistance was validated in yeast model, suggesting their potential for improving drought stress tolerance. These findings substantially advance our mechanistic understanding of drought adaptation in qingke while providing novel insights and valuable genetic resources for molecular breeding programs targeting abiotic stress resistance in barley and related cereal crops.